Uncommon Molecular Structures for Organic Electronics: Cross-Conjugated Biradical Dianions and Mechano-Made Biradicals - Casado-Cordón, Juan (My University, 2017)
Significant advances in any field of research often come from unexpected experimental results. We all know that uncommon behaviors are destined to envisage new applications whereas collection of typical features only helps to improve existing ones. There are plenty of examples of this in the field of organic electronics such as the discovery of conductivity in PA, the behavior of PCBM as electron acceptor in bulk heterojunction solar cells or singlet fission for second generation photovoltaics. The two findings I will describe here are not obviously of comparable importance but allow me to introduce the reader in the topic of the talk.
Keywords: Electrónica; Diradical; Raman spectroscopy; electronic structure